شریعت اور رائج قانون میں شادی کےلئے عمر کا تعین: ایک تقابلی جائزہ: etermination of Marriage Age in Islamic Sharīah and Prevailing Law: A Comparative Review - Akram, Muhammad Farooq; Nawaz, Dr. Rab (Al-Amīr Research Journal for Islamic Studies, 2023)
This article comprises of discussion regarding puberty and age of marriage in Islamic Sharīah and current applied law. In Islam recognition of adolescence (bulūghat) has been determined with the different factors and reasons after that practices of Sharīah are obligatory. Current prevailing law is also charged with some restrictions concerning the age of marriage. In this comparative analysis, we came to know that there are some discrepancies between legal proceedings from both sides. This study finds that Islamic Sharīah incorporates multiple aspects to declare the age of puberty as compared to the law of the time. Both male and female genders are subject to different ages of marriage. In Islam symptoms of puberty are central to the age of marriage. There is no puberty before 12 years for male and 9 years for female genders. Depending upon the situation there are several factors to justify the age of marriage well-elaborated in Islamic jurisprudence. Keywords: Marriage, Puberty, Sharīah, Prevailing law, Comparison